Modern perspectives on cell therapy using exosomes in experimental traumatic brain injury - Prus, I.; Appelhans, O.; Prus, R.; Toporova, O. (Journal of Education, Health and Sport, 2026)
Traumatic brain injury (TBI) remains one of the leading causes of mortality and long-term disability worldwide, particularly among young and working-age populations. Despite significant advances in neurocritical care and neurosurgical techniques, effective therapeutic strategies aimed at promoting neural repair and preventing the secondary systemic consequences of TBI remain limited. This review provides a comprehensive overview of current experimental approaches to cell-based therapy for TBI, with particular emphasis on mesenchymal stem cells (MSCs) and MSC-derived exosomes. The pathophysiology of TBI involves primary mechanical injury followed by a complex cascade of secondary pathological events, including neuroinflammation, hypoxia, oxidative stress, and disturbances in cerebral microcirculation. Microglial activation is considered a key driver of secondary brain injury, contributing to sustained neuroinflammatory responses and subsequent neurodegenerative changes. Although endogenous regenerative mechanisms, including activation of neural stem cells and the release of neurotrophic factors, are initiated following injury, they are insufficient to achieve complete functional recovery. MSCs have demonstrated considerable therapeutic potential owing to their ability to home to injured tissues, modulate inflammatory responses, and promote neuroregeneration. More recently, increasing attention has focused on MSC-derived exosomes, which represent a promising cell-free therapeutic alternative with several favorable characteristics, including low immunogenicity, high stability, and the capacity to cross the blood–brain barrier. Experimental studies have demonstrated that exosomes transfer bioactive molecules, including RNAs and proteins, to recipient cells, thereby modulating gene expression and promoting functional recovery. In conclusion, MSC-derived exosomes represent a promising and rapidly evolving therapeutic strategy for the treatment of TBI and its systemic consequences. Nevertheless, further experimental studies are required to elucidate their mechanisms of action, biodistribution, and interactions with target cells in both the central nervous system and peripheral organs.